Aviturismo como alternativa de desarrollo para el corredor hídrico Carrizal-Chone - Cantos Basurto, María Isabel (2021)
This research aimed to design a bird tourism product as an alternative for tourism development for the Carrizal-Chone water corridor, the work is of a mixed nature (quantitative and qualitative), with a descriptive exploratory approach. For the development of the project, the tourist characterization of the study area was carried out, where it was possible to know the current situation of the Carrizal -Chone water corridor (Sixto Durán Ballén “La Esperanza” Dam, La Segua Wetland and Isla Corazón y Fragatas Wildlife Refuge). Through direct observation and bibliographic review, it was found that there are shortcomings in tourism management, deficient local public policies that discourage the growth of entrepreneurs and tourism products; but the ecosystem diversity and its potential for bird tourism were also identified, various techniques and tools were used such as: SWOT matrix, stakeholder matrix, 10 interview questionnaires with local managers, also reference was made to the area identifying points of interest for cartography. Then the registration and cataloging of bird species were obtained, for this purpose bird inventory cards and binoculars were used, identifying 123 types of species, representing 36 families along the corridor. In addition, the demand was studied where the perception and profile of the visitor was known by applying 384 surveys. In the last phase, a bird tourism product was proposed for the Carrizal-Chone water corridor. Strategies for the dissemination, promotion and commercialization of the avitourism product were proposed. This is to diversify the offer of alternative products in the area.